A Differential Calculus on the (h, j)-Deformed Z3-Graded Superplane - Celik, Salih; Celik, Sultan; Cene, Erhan (SPRINGER BASEL AG, 2014)
In this work, Z(3)-graded quantum (h, j)-superplane is introduced with a help of proper singular g matrix and a Z(3)-graded calculus is constructed over this new h-superplane. A new Z(3)-graded (h, j)-deformed quantum (super)group is constructed via the obtained calculus.
Keywords: q-superplane; Z(3)-graded quantum superplane; h-deformation; DEFORMATION; Mathematics; Physics